Feasibility and outcome of laser CO2 conization performed within the 18th week of gestation. Issue 1 (1st January 2007) - Fambrini, M.; Penna, C.; Fallani, M. G.; Pieralli, A.; Mattei, A.; Scarselli, G.; Taddei, G. L.; Marchionni, M.
Abstract : The purpose of this study is to evaluate the feasibility, safety, and potential therapeutic benefit of laser CO2 conization of the cervix for in situ and minimally invasive carcinoma diagnosed during pregnancy. Twenty-six pregnant patients with biopsy-proven carcinoma in situ /cervical intraepithelial neoplasia III but colposcopically suspicious for invasion underwent laser CO2 conization during the 18th week of gestation in an outpatient setting under local anesthesia. No major intraoperative or postoperative complications occurred, and cervical cerclage was not required in any case. Two cases (7.7%) of occult FIGO stage IA1 minimally invasive cervical cancers with free surgical margins were diagnosed. Both patients delivered vaginally at term and were free of disease at postpartum follow-up. Median length of gestation was 39.1 weeks with a median birth weight of 3450 g. All 1-min Apgar scores were 8 or greater. Twenty patients (76.9%) delivered vaginally, while six patients underwent cesarean section for indications not related to the prior conization. After a mean postpartum follow-up of 18 months (range 3–42), 92.3% of patients continued to have both cytologic and colposcopic evaluations negative for persistent or recurrent disease. Two cases of persistent intraepithelial disease were successfully managed by reconization. In summary, our data suggest that laser CO2 conization performed within the 18th week of gestation is safe for both the patient and the fetus, provides reliable histologic diagnosis, and can be curative. Further studies are required to confirm the favorable risk–benefit ratio of laser CO2 conization in the management of non-reassuring cervical lesions observed in the first half of pregnancy.